Production of mexican brown macroalgae fucoidan and fucosidases under an integral green technology bioproceses by the biorefinery concept - Rodríguez-Jasso, Rosa M. (2015)
Marine ecosystem can be considered a rather exploited source of natural substances with enormous bioactive potential. In Mexico macro-algae study remain forgotten for research and economic purposes besides the high amount of this resource along the west and east coast. For that reason the Bioferinery Group of the Autonomous University of Coahuila, have been studying the biorefinery concept in order to recover high value byproducts of Mexican brown macro-algae including polysaccharides and enzymes to be applied in food, pharmaceutical and energy industry. Brown macroalgae are an important source of fucoidan, alginate and laminarin which comprise a complex group of macromolecules with a wide range of important biological properties such as anticoagulant, antioxidant, antitumoral and antiviral and also as rich source of fermentable sugars for enzymes production. Additionally, specific enzymes able to degrade algae matrix (fucosidases, sulfatases, aliginases, etc) are important tools to establish structural characteristics and biological functions of these polysaccharides. The aims of the present work were the integral study of bioprocess for macroalgae biomass exploitation by the use of green technologies as hydrothermal extraction and solid state fermentation in order to produce polysaccharides and enzymes (fucoidan and fucoidan hydrolytic enzymes). This work comprises the use of the different bioprocess phases in order to produce high value products with lower time and wastes.